2017
DOI: 10.3389/fncel.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing of the Human Retinae Reveals the Expression of Odorant Receptors

Abstract: Several studies have demonstrated that the expression of odorant receptors (ORs) occurs in various tissues. These findings have served as a basis for functional studies that demonstrate the potential of ORs as drug targets for a clinical application. To the best of our knowledge, this report describes the first evaluation of the mRNA expression of ORs and the localization of OR proteins in the human retina that set a stage for subsequent functional analyses. RNA-Sequencing datasets of three individual neural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
(103 reference statements)
3
19
0
Order By: Relevance
“…The reason for the inclusion of photoreception-related genes within the expression profile of the olfactory bulbs remains unclear; however, it is likely that genes involved in the olfactory and photoreception systems may share similar signal transduction function in both tissues. This hypothesis is supported by at least two other studies that reported the expression of olfactory genes in the visual system (Jovancevic et al, 2017;Pronin et al, 2014).…”
Section: Effects Of Elevated Co 2 On Gene Expression In the Salmon supporting
confidence: 66%
“…The reason for the inclusion of photoreception-related genes within the expression profile of the olfactory bulbs remains unclear; however, it is likely that genes involved in the olfactory and photoreception systems may share similar signal transduction function in both tissues. This hypothesis is supported by at least two other studies that reported the expression of olfactory genes in the visual system (Jovancevic et al, 2017;Pronin et al, 2014).…”
Section: Effects Of Elevated Co 2 On Gene Expression In the Salmon supporting
confidence: 66%
“…The datasets were summarized, and the expression data are presented as the means of the FPKM values (mFPKM). The neural retina raw data were taken from an earlier study (Jovancevic et al, 2017b ). All the datasets were equivalently analyzed with the same parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The datasets were visualized and investigated by the Integrative Genomic Viewer ( http://software.broadinstitute.org/software/igv/ ) for proving sequence alignments and for the correct mapping of reads for the top expressed genes. We determined a cutoff value of 0.3 FPKM for OR expression as described in Jovancevic et al ( 2017b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we noticed that the expression patterns of the three ORs differ between skin explants and epidermis. Specific distribution of various ORs was also previously reported in the human eye, where OR10AD1, OR6B3, and OR5P3 can be found in different retina cell types [ 32 ]. Similarly, in human spermatozoa, different OR proteins are localized at distinct specialized cellular compartments such as the equatorial segment, the midpiece, and the tail [ 33 ].…”
Section: Discussionmentioning
confidence: 56%